Prestressed Precast Hollow-Core Slabs with Different Shear Span to Effective Depth Ratio - Jasim Mahmood Mhalhal (Wasit Journal of Engineering Sciences)
Four full scale precast prestressed hollow-core slabs were tested under the influence of four lines loading with various values of shear span to effective depth ratio (a/d) (1.5, 2, 3.5 and 5). The dimensions of the hollow-core slab were 2000 mm, 1200 mm and 150 mm (length, width and thickness, respectively). All slabs were cast with a high compressive strength concrete of approximately 79.5 MPa. Experimental test results showed four patterns of failure mode depending on the ratio of (a/d). They were flexural failure, flexure-shear failure and shear compression failure. In addition to combination failure between tension shear and anchorage failure, accompanied by sliding strand in concrete. The failure loads decreased about 19.6% as (a/d) increased by 233.3%.  Finally, the highest first crack load, 110kN, was recorded for sample, HCS 1.5, having the lowest (a/d) ratio.